Failing in Creativity: The Problem of Policy and Practice in Australia and the United States. (2nd January 2019) - Henriksen, Danah; Creely, Edwin; Henderson, Michael
Abstract: Considering the political environments of Australia and the United States, the authors discuss the disconnect between policy and the practical needs of educators for creativity in the classroom.